Bendamustine + rituximab chemoimmunotherapy and maintenance lenalidomide in relapsed, refractory chronic lymphocytic leukaemia and small lymphocytic lymphoma: A Wisconsin Oncology Network Study. (23rd February 2016) - Chang, Julie E.; Havighurst, Thomas; Kim, KyungMann; Eickhoff, Jens; Traynor, Anne M.; Kirby‐Slimp, Rachel; Volk, Lynn M.; Werndli, Jae; Go, Ronald S.; Weiss, Matthias; Blank, Jules; Kahl, Brad S.
Summary: Bendamustine + rituximab (BR) has demonstrated high response rates in relapsed/refractory (R/R) chronic lymphocytic leukaemia (CLL) and small lymphocytic lymphoma (SLL). However, progression‐free survival (PFS) after BR is <18 months. This study was designed to determine if maintenance lenalidomide after BR induction could improve PFS in R/R CLL/SLL. Thirty‐four patients with R/R CLL/SLL who had received 1–5 prior chemotherapy regimens were treated with 6 cycles of BR induction. Patients achieving at least a minor response received twelve 28‐d cycles of lenalidomide 5–10 mg/d. The primary endpoint was PFS. The median age was 67 years, with a median of 2 prior therapies. Eleven patients had confirmed presence of 17p and/or 11q deletions. Twenty‐five (74%) completed 6 cycles of induction BR (response rate 56%). Nineteen (56%) patients received maintenance lenalidomide; only 6 patients completed the intended 12 cycles, highlighting the limited feasibility of lenalidomide in this setting, primarily due to haematological and infectious toxicities. The observed median PFS of 18·3 months is not significantly different from that of BR induction in R/R CLL/SLL without maintenance therapy (15·2 months). It is possible that lenalidomide maintenance may be more feasible and effective in the front‐line setting, which is being tested in an ongoing trial (NCT01754857).